Loss and reliability analysis of various solid-state battery reconfiguration topologies - Yang, Xu; Liu, Zhicheng; Zhu, Jin; Liu, Pei; Wei, Tongzhen (Frontiers in Energy Research, 2023)
The research domain about the selection and design methodology of battery topology structures for energy storage systems, grounded in practical application scenarios, remains significantly underexplored. Furthermore, a substantial gap exists in the current state of research, where the majority of studies lack a comprehensive analysis of losses and reliability associated with reconfigurable battery topology structures. This paper quantitatively analyzes existing MOSFET-based topologies from three key dimensions: losses, costs, and reliability. The study aims to discern the impact of different topology structures and energy storage systems with redundant units on these three dimensions. Subsequently, while ensuring the adaptability of the topology structure, we propose a novel reconfigurable battery system topology suitable for DC microgrids, accompanied by its corresponding control strategy. Through comparative analysis with three typical topology structures, this topology structure has been validated to exhibit certain advantages in terms of losses, reliability, and costs. Lastly, the feasibility of the introduced topology structure is demonstrated through simulation using MATLAB/Simulink. Simulation results indicate that the proposed topology structure not only provides precise control of charge and discharge currents but also demonstrates excellent battery balancing capabilities.